Immunogenicity and Protective Efficacy of a Fusion Protein Tuberculosis Vaccine Combining Five Esx Family Proteins - Xiang, Zhi-hao; Sun, Rui-feng; Lin, Chen; Chen, Fu-zeng; Mai, Jun-tao; Liu, Yu-xiao; Xu, Zi-yan; Zhang, Lu; Liu, Jun (Frontiers in Cellular and Infection Microbiology, 2017)
One strategy to develop the next generation of tuberculosis vaccines is to construct subunit vaccines based on T cell antigens. In this study, we have evaluated the vaccine potential of a fusion protein combining EsxB, EsxD, EsxG, EsxU and EsxM of Mycobacterium tuberculosis (M. tb). This recombinant protein, named BM, was expressed in and purified from Escherichia coli. Immunization of C57BL/6 mice with purified BM protein formulated in Freund’s incomplete adjuvant induced the production of Th1 cytokines (IFN-γ, TNF, and IL-2) and multifunctional CD4+ T cells. Vaccination of BALB/c mice with BM protein followed by intravenous challenge with Mycobacterium bovis BCG resulted in better levels of protection than the two leading antigens, Ag85A and PPE18. Taken together, these results indicate that BM is a protective antigen. Future studies to combine BM with other antigens and evaluate its effectiveness as a booster of BCG or as a therapeutic vaccine are warranted.